Mental Health Assessment Model for College Students Using Circular q-Rung Orthopair Fuzzy Muirhead Means and MULTIMOORA Method - Gou Ying (IEEE Access)
This work investigates the enhanced MULTIMOORA technique using the circular q-rung orthopair fuzzy set (Cq-ROFS) for mental health assessment among college students. Recently, Cq-ROFS was proposed as the development of circular Pythagorean FSs (C-PFSs), circular intuitionistic FSs (C-IFSs), and circular rung orthopair FSs (q-ROFSs). However, they are only considered for a few essential algebraic characteristics. In the present paper, we extend our investigation on circular q-ROFSs (Cq-ROFSs) within Muirhead mean aggregation operators (AOs) by incorporating additional algebraic law mathematical features. These include the circular q-rung orthopair fuzzy (Cq-ROF) weighted Muirhead mean (Cq-ROFWMM) and Cq-ROF dual weighted Muirhead mean (T-SFDWMM) aggregation operators (AOs). To compute the essential aspects, we apply the MULTIMOORA technique, incorporating the proposed operators for Cq-ROF numbers (Cq-ROFNs), enhancing the value and effectiveness of the evaluation process. Employing the proposed Cq-ROF MULTIMOORA model to select the best mental health treatment options based on different attributes such as student engagement, evidence-based effectiveness, and accessibility and inclusivity. The ranking results indicate that $~{{\vert\!\!\!G}}{_{1}}$ is the most effective treatment model, outperforming all other alternatives across the evaluation criteria. A real-world case study demonstrates the proposed method’s practical applicability and reliability in selecting optimal mental health strategies. Additionally, sensitivity analysis confirms the model’s stability, making it a valuable tool for evidence-driven mental health policy and intervention planning in educational settings.